The clinical classification of patients with acute heart failure at emergency department and its relation with management and outcome: a cross sectional study from Syria - Mohammad Aldli; Mohammad Alsultan; MhdAmin Alkhatib (BMC Cardiovascular Disorders)
Abstract Introduction To compare the clinical characteristics and outcomes of patients with acute heart failure (AHF) according to the 2016 European Society of Cardiology (ESC) guidelines taking into account isolated right HF (RHF) with left HF (LHF) phenotypes. Volume status was assessed by the clinical manifestations and lung ultrasound (LUS). The secondary aim was to study the role of echocardiography in congestion based on LUS and their relations with outcomes. Methods This study included AHF patients, who referred to the emergency department (ED) at AL-Mouwasat and AL-Assad University Hospitals in Syria between May and August 2024. The same cardiologist reviewed medical reports, signs/ symptoms of decompensation, echocardiographic assessment, diagnosis, and treatment therapies. Results Of 100 patients, 10 patients (10%) had isolated RHF and 90 patients (90%) had LHF, including warm-wet (n = 65, 65%), followed by cold-wet (n = 13, 13%), warm-dry (n = 10, 10%), and cold-dry (n = 2, 2%). Most discharged patients without admission were Warm-dry, meanwhile most of patients with cold-wet (76.9%) were admitted to intensive care unit (ICU). The longest in-hospital stays were in cold-wet (11.9 days) followed by isolated RHF (7.5 days). While in-hospital mortality was mainly in cold-wet (38.5%) followed by isolated RHF (20%). Diuretics dose was highest in cold-wet followed by isolated RHF, while hydration was predominantly in cold-wet. Using vasopressors and inotropes were predominantly in cold-wet. Systolic blood pressure (SBP), hemoglobin (Hb), sodium (Na), proximal right ventricular outflow tract (RVOT1), left ventricular end-diastolic internal diameter (LVIDd), Tricuspid annular systolic plane excursion (TAPSE), and systolic pulmonary atrial pressure (SPAP) correlated with hospital stays, while only SBP and Cr correlated with in-hospital mortality. The cut-off values of E/e’ ratio, isovolumic relaxation time (IVRT), and deceleration time (DT) were (12.5, 55ms, and 131.5 ms; respectively) and could predict congestion (guided by LUS) with sensitivities of (96%, 74%, and 62%; respectively) and specificities of (53%, 92%, and 84%; respectively). Conclusion Classifying AHF patients into these five groups, based on clinical examination supporting by echocardiography and LUS evaluation can give better assessment of the AHF phenotypes and gives more details for management. The bedside diagnostic assessment by LUS and echocardiography is an easy tool and seems to be of great benefit in detecting congestion that enhances the treatment protocols.